LITERATURE REVIEW OF BULLYING ASSESSMENT : A CRITICAL REVIEW OF THE INVENTORY OF BULLYING SCALE IN SCHOOLS: KAJIAN LITERATUR ASSESSMENT BULLYING: TINJAUAN KRITIS TERHADAP INVENTORI SKALA BULLYING DI SEKOLAH - Ratna Wulandari; Desi Yunita Putri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Bullying is still a serious problem in Indonesia. The impact of bullying on its victims is very real. Meanwhile, on average, educators, especially guidance counselors, education staff, and parents only become aware of bullying after it has happened. If early detection efforts are made, the case can be anticipated earlier. This is because there are no measurement instruments that can assist the counseling teacher in detecting cases of bullying that occur easily and on a large scale. So it is necessary to digitize the bullying scale instrument. Instruments in the form of self-reports are the most commonly used method in collecting data to assess bullying phenomena. This method has several advantages. The Olweus Bully/Victim Questionnaire (OBVQ) is one of the most widely used instruments to measure the prevalence of bullying worldwide. This questionnaire provides students with a clear definition of bullying that includes three important characteristics: (1) intent to harm others; (2) repetitive behavior; and (3) the power imbalance between victims and perpetrators. The OBVQ can be adapted into a bullying scale inventory that is appropriate to the conditions and culture in Indonesia so that it can be used to detect bullying phenomena that occur in Indonesian youth, especially at school.